Hubungan Sikap Dengan Pengetahuan Remaja Tentang Kesehatan Reproduksi - Wahyuni, Sri; Latif, Sarifudin Andi; Rihi, Pryati; Mildaratu, Mildaratu; Hilal, Achmad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The globalization of information through the media has caused changes in the sexual behavior of teenagers in general. Sexual exploitation in television, magazines, video clips, online media and films influences many young people to engage in sexual activities freely. Media penetration of changes in adolescent sexual behavior due to not being accompanied by adequate sex education both at home by parents and at school by teachers. The aim of this research is to determine the attitude factor analysis of adolescent knowledge about reproductive health. This type of research uses quantitative research, this research uses a cross sectional research design, which is research that studies the correlation between exposure or risk factors (independent) and consequences or effects (dependent), with data collection carried out simultaneously at one time between risk factors and the effect (point time approach). The population and sample in this study were all teenagers who lived in the working area of the Padongko Health Center, Barru Regency, totaling 82 people and the sampling technique used was accidental sampling. The results of the research to look at the Chi-Square table, obtained (dk) or (df) = 1 and the significance level was set at 0.05, so the Chi-Square table value was 49.801. Based on the results of the Chi-Square test, it was found that the calculated Chi-Square value was smaller in the Chi-Square table (4,880 < 49,801). Based on this value because the calculated chi-square value < chi-square table, it can be concluded that adolescent knowledge is related to reproductive health. . Based on the results of the analysis of the asymp.sig value of 0.027 < 0.05, it can be concluded that adolescent knowledge is related to reproductive health. Suggestions for the midwife profession can increase its role in providing health education and counseling regarding adolescent reproductive health.